2022
DOI: 10.3390/jcm11123380
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Complicated Grief, and Associated Factors, of Bereaved Family Members of Patients Who Died of Malignant Pleural Mesothelioma in Japan

Abstract: Objectives: we investigated the prevalence and associated factors of depression and complicated grief (CG) among bereaved family members of malignant pleural mesothelioma (MPM) patients in Japan. Methods: Bereaved family members of MPM patients (n = 72) were surveyed. The Japanese version of the Patient Health Questionnaire-9 (PHQ-9) and the Japanese version of the Brief Grief Questionnaire (BGQ) were used to assess depression and complicated grief (CG), respectively. Socio-economic factors, anger toward asbes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…This should cover exploring barriers to access and the type/effectiveness of interventions, including whether these are trauma-informed. The need for further multi-site research on complicated grief after the death of a loved one from mesothelioma has been recommended (Nagamatsu et al, 2022), and we echo this in the European context. Lastly, the issue of scanxiety in mesothelioma has not yet been explored, despite being a key concern of patients and carers.…”
Section: Recommendations For Future Researchmentioning
confidence: 65%
See 2 more Smart Citations
“…This should cover exploring barriers to access and the type/effectiveness of interventions, including whether these are trauma-informed. The need for further multi-site research on complicated grief after the death of a loved one from mesothelioma has been recommended (Nagamatsu et al, 2022), and we echo this in the European context. Lastly, the issue of scanxiety in mesothelioma has not yet been explored, despite being a key concern of patients and carers.…”
Section: Recommendations For Future Researchmentioning
confidence: 65%
“…Our finding that carers had worse depression than patients chimes with Moore et al's (2023) study, which indicated 74% of carers for mesothelioma patients were at risk of depression, linked to the burden of caregiving plus impacts on their own physical health and employment. A recent study of depression and complicated grief in family members of mesothelioma patients, Nagamatsu et al (2022) reported that 19% of participants had depression, with higher scores for those who had not received financial compensation. Complicated grief (intense grief lasting longer than usual and causing impairment in daily functioning) was more likely in those who did not receive compensation, who's relative had surgery, and who were dissatisfied with their care when critically ill.…”
Section: Contribution To Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the experience of MM specifically, the poor prognosis, reduced effectiveness of treatments, occupational etiology, poor quality of life for those in the latter stages of the disease, and advanced age at diagnosis exacerbate the psychological impact and make the experiences of individuals and family members even more problematic (Bonafede et al, 2020;Demirjian et al, 2024;Nagamatsu et al, 2022;Warby et al, 2019). Both patients and their families may experience somatic and psychosomatic symptoms, impaired quality of life, anxiety, depression, fear, and mistrust as well as post-traumatic symptoms (Bonafede et al, 2022;Demirjian et al, 2024;Gonzalez-Ling et al, 2023;Nagamatsu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the experience of MM specifically, the poor prognosis, reduced effectiveness of treatments, occupational etiology, poor quality of life for those in the latter stages of the disease, and advanced age at diagnosis exacerbate the psychological impact and make the experiences of individuals and family members even more problematic (Bonafede et al, 2020;Demirjian et al, 2024;Nagamatsu et al, 2022;Warby et al, 2019). Both patients and their families may experience somatic and psychosomatic symptoms, impaired quality of life, anxiety, depression, fear, and mistrust as well as post-traumatic symptoms (Bonafede et al, 2022;Demirjian et al, 2024;Gonzalez-Ling et al, 2023;Nagamatsu et al, 2022). We strongly believe that an interdisciplinary approach to the treatment of MM is fundamental to restore and promote in both patients and caregivers the ability to tolerate, symbolize, mentalize and narrate the traumatic effects of the disease, but also the vital aspects that live on in them and in their relationships (Granieri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%